Design and analysis of automated storage and retrieval system mast - Demirel, Ozan Erdem (My University, 2022)
Depolama sistemlerinde; ürünlerin teslim alınması, yerleştirilmesi, sayımı, toplaması, kontrolü ve gönderilmesi gibi adımlar yer almaktadır. Otomatik depolama sistemleri sayesinde depolarda harcanan ölü alanlar azaltılmakta ve standart forklift sistemlerinin ulaşamayacağı yüksekliklerde yüksek kapasiteli depolama yapılabilmektedir. Standart depolarda istenilen yüksek taşıma kapasiteleri +500kg , hızlar 4m/ s ve ivmelenmeler 2 m/ s2 sebebiyle robotik sistemlerde oldukça yüksek dinamik yükler ortaya çıkmaktadır. Yatırım maliyetleri sebebiyle sistemlerin ağırlığının düşürülmesi göz önünde bulundurulduğunda robotik sistemin kule tasarımında katılığının (rijitlik, stiffness) azalmasıyla durumuyla karşılaşılmakta ve bu sebeple sistemde yüksek titreşimlere sebep olmaktadır. Yapılan çalışmada otomatik depolama sisteminde kullanılan kule üzerine yoğunlaşılmış ve yapının tasarım ve analizi yapılmıştır. Basit mesnet olarak modellenen kule tasarımında; tasarım isterleri dahilinde, rijitlik, ağırlık ve boyut gibi parametrelerin optimizasyonunun yapılması hedeflenmektedir. Yapılan tasarımda dinamik kuvvetler, depolama kulesi yapısının incelenmesi, sistemin matematik modelinin çıkarılması, kontrol algoritmasının oluşturulması konuları ile tasarım tamamlanmıştır. Sonuç olarak bir otomatik depolama sisteminde kullanılan robotik sistemin tasarımı ile ilgili parametreler değerlendirilmiş ve titreşim kontrolünün yapılmasıyla sisteminin hızının optimal şekilde kullanılmasına ulaşılmıştır.

In automated storage systems, there are steps such as receiving, placing, counting, collecting, controlling, and sending the products. Thanks to automatic storage systems, dead spaces in warehouses are reduced, operator errors can be prevented, and high-capacity storage can be made at heights that standard forklift systems cannot reach. Established warehouses can be designed in various configurations according to the number of hourly product transfers expected from the system, and appropriate robotic systems are integrated into the system accordingly. Due to the high carrying capacities (+500kg), speeds (+4 m/ s) and accelerations (+2m/ s2) required in standard warehouses, very high dynamic loads arise in robotic systems. Considering the investment costs, it is quite normal to want to reduce the weight of every robotic system. Considering the same situation in these systems, the robotic system is faced with a decrease in the stiffness (rigidity) in the tower design, and therefore it causes high vibrations and wobbles in the system. In the work to be done, the tower used in the automatic storage system was focused on and the design and analysis of the structure was made. In the tower design modelled as a simple support; It is aimed to optimize parameters such as stiffness, weight, and size within the design requirements. The design was completed with dynamic forces, examination of the storage tower structure, mathematical modelling of the system, and creation of the control algorithm. As a result, parameters related to the design of the robotic system used in an automatic storage system were evaluated and an optimal evaluation of the speed of the system was achieved by performing vibration control.
Keywords: asrs; depolama sistemi; Makine mühendisliği; Mechanical engineering; stacker crane; titreşim kontrol; vibration control